Criminal Law Settlement Through Restorative Justice in Indonesia in Terms of Justice and Legal Certainty - Mega Jaya, Arizon; Mega Jaya, Aristama (International Asia Of Law and Money Laundering, 2024)
The win lose solution nature of the criminal justice process often leads to disappointment. In addition, the judicial process, which is expected to be a formal way, turns out to be expensive, prolonged, tiring and sometimes does not solve the problem. From this phenomenon, efforts to reform the national criminal law are needed, one of which is the concept of